2004
DOI: 10.1038/sj.gt.3302236
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor decoy for AP-1 reduces mesangial cell proliferation and extracellular matrix production in vitro and in vivo

Abstract: Diabetic nephropathy is characterized by an expansion of glomerular mesangium, caused by mesangial cell proliferation and excessive accumulation of extracellular matrix (ECM) proteins, which eventually leads to glomerulosclerosis and renal failure. Activator protein-1 (AP-1), a transcription factor, is implicated in the transcriptional regulation of a wide range of genes participating in cell proliferation and ECM production. This investigation was undertaken to test the hypothesis that AP-1 plays an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…Blunted activation of NF-B may lead to glomerular cell apoptosis that is required for clearance of excessive mesangial cells during the resolution of mesangial proliferative glomerulonephritis (49). Similarly, lack of AP-1 activation may lead to suppression of glomerular cell proliferation (50). The attenuated activation of NF-B and AP-1 in macrophage-primed mesangial cells can also cause attenuated expression of chemokines, leading to reduction in the number of glomerular macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Blunted activation of NF-B may lead to glomerular cell apoptosis that is required for clearance of excessive mesangial cells during the resolution of mesangial proliferative glomerulonephritis (49). Similarly, lack of AP-1 activation may lead to suppression of glomerular cell proliferation (50). The attenuated activation of NF-B and AP-1 in macrophage-primed mesangial cells can also cause attenuated expression of chemokines, leading to reduction in the number of glomerular macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…p3TP-lux (TGF-b1 promoter construct) was described previously. 45 To analyze luciferase expression, the cells were washed twice with PBS and lysed in 200 ml of 1 Â reporter lysis buffer (Promega). Each lysate (50 ml) was examined for luciferase activity by means of a commercial kit (Promega).…”
Section: Suppression Of Rat Kidney Fibrosis By Sp1 Decoy Y-m Chae Et Almentioning
confidence: 99%
“…We previously reported that an AP-1 decoy oligonucleotide which specifically binds intracellular AP-1 inhibits AP-1 transcription and cell invasion as effectively as ascochlorin [20]. We have shown that our decoy strategy effectively inhibits specific transcription factor activity and pathogenic disorders in vivo [35]. A genetic strategy targeting AP-1 activity also might be effective for treatment of ERnegative breast cancers.…”
Section: Discussionmentioning
confidence: 99%